2020
DOI: 10.1186/s12889-020-8235-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices assessment of malaria interventions in rural Zambia

Abstract: Background: Despite rapid upscale of insecticide-treated nets (ITNs) and indoor residual spraying (IRS), malaria remains a major source of morbidity and mortality in Zambia. Uptake and utilization of these and novel interventions are often affected by knowledge, attitudes and practices (KAP) amongst persons living in malariaendemic areas. The aims of this study were to assess malaria KAP of primary caregivers and explore trends in relation to ITN use, IRS acceptance and mosquito density in two endemic communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…Concerning the use of interpersonal conversation in Bertoua and Kaélé, it is likely that the frequent shortage of electric power in these cities at the time of the study may have promoted this communication means. Studies in South Africa and Zambia indicated that health facilities could also serve as a primary source of information on malaria [ 8 , 31 ]; however, just few participants went to hospitals to look for information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the use of interpersonal conversation in Bertoua and Kaélé, it is likely that the frequent shortage of electric power in these cities at the time of the study may have promoted this communication means. Studies in South Africa and Zambia indicated that health facilities could also serve as a primary source of information on malaria [ 8 , 31 ]; however, just few participants went to hospitals to look for information.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mortality in healthcare facilities decreased from 25% in 2013 to 14.6% in 2018 [5]. However, despite the increased scale-up of ITNs, residual malaria transmission remains a challenge in most epidemiological settings with high malaria incidence [8][9][10]. Several factors could be responsible for the subperformance of current control interventions.…”
Section: Introductionmentioning
confidence: 99%
“…We found that more than 80% of the respondents were aware that the use of ITNs could prevent malaria. This observation has been made by N'dri et al (2020) and Jumbam et al (2020). However, only The respondents reluctance to sleep under ITNs was because it impaired breathing and generated heat.…”
Section: Discussionmentioning
confidence: 55%
“…Also, most respondents allowed children and adults to sleep under ITNs and this practice has been observed elsewhere by different authors (Owusu et al, 2018 ;Jumbam et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
“…15 Together, these results highlight the potential for SRs to reduce a variety of vector-borne diseases, augment existing public health efforts and be an effective component of vector control intervention strategies. To help guide implementation and programmatic scale-up, additional assessments, which have already begun, [26][27][28][29] are needed.…”
mentioning
confidence: 99%